Failure analysis methodology on donut pattern failure due to photovoltaic electrochemical effect. (September 2017) - Neo, S.P.; Quah, A.C.T.; Ang, G.B.; Nagalingam, D.; Ma, H.H.; Ting, S.L.; Soo, C.W.; Chen, C.Q.; Mai, Z.H.; Lam, J.C.
Abstract: This paper described a low yield case which resulted in a donut shape failing pattern. It also described a scenario where static fault localization is ineffective and a systematic problem solving approach based on symptoms, induction, hypothesis and verification was engaged to resolve the issue with understanding on the root cause and the failure mechanism. The low yield is due to residual light in the dilute HF clean tool which results in photovoltaic electrochemical effect on the exposed metal, through via holes, connecting to large PN junction. This results in subsequent resistive via formation and analogue failure. Highlights: Systematic problem solving approach based on symptoms, induction, hypothesis and verification. Method resolved challenging excursion issue due to process drift in DHF clean with root cause understanding Subtle photocorrosion induced subtle void and hillock on specific analogue structures Method applied successfully in scenario where static fault isolation was ineffective & dynamic techniques unavailable. Case stresses the importance of light free environment in Cu damascene process